2020
DOI: 10.1002/acr.24023
|View full text |Cite
|
Sign up to set email alerts
|

Lupus Low Disease Activity State and Reduced Direct Health Care Costs in Patients With Systemic Lupus Erythematosus

Abstract: Objective Treat‐to‐target end points for systemic lupus erythematosus (SLE) have been assessed for their impact on damage accrual and flare, but whether they have an impact on the high health care utilization and costs in SLE has not been studied. The purpose of this study was to examine our hypothesis that the recently described lupus low disease activity state (LLDAS) would be associated with reduced health care cost. Methods Data from a single tertiary hospital longitudinal SLE cohort were assessed. Baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…44 Finally, remission and LDA could reduce hospitalisation rate; this has been reported in the Peruvian Almenara Lupus cohort 28 ; LDA could also reduce annual medical cost as reported in a study from an Australian cohort. 41 It is important to point out that this information needs to be confirmed in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…44 Finally, remission and LDA could reduce hospitalisation rate; this has been reported in the Peruvian Almenara Lupus cohort 28 ; LDA could also reduce annual medical cost as reported in a study from an Australian cohort. 41 It is important to point out that this information needs to be confirmed in other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Disease progression is associated with multiorgan involvement, including the central 9 . Greater disease severity in related disorders, such as rheumatoid arthritis, has also been associated with greater medical costs 15 , and spending ≥ 50% of the time in a low disease activity state has been associated with a 25.9% reduction in annual direct medical costs for patients with SLE 16 . Over the study period from 2012 to 2015, annual total healthcare costs generally remained the same.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the risk of damage decreases with the length of time in either LLDAS or remission. While low disease activity intuitively appears to be a less desirable outcome than remission, patients in the LLDAS nevertheless achieve significantly better scores on both the SLE Quality of Life questionnaire and the 36-item Short Form Health Survey [ 76 ], reduced direct healthcare costs [ 77 ], damage and mortality than those with active disease [ 78 ]. Importantly, patients who spent even a short time in clinical remission (even <25% of visits) had a significant decrease in the rate of damage compared with never achieving remission.…”
Section: Long-term Outcomes In Sle: Trends Over Time and Major Contrimentioning
confidence: 99%